Descriptive epidemiology of injuries in Japanese male collegiate rugby union players - Ryo Ogaki; Gento Otake; Satoko Nakane; Yukiko Kosasa; Yosuke Kanno; Ayane Ogura; Masahiro Takemura (Japanese Society of Physical Fitness and Sports Medicine, 2020)
To the best of our knowledge, most previous studies regarding the epidemiology of injuries in rugby union (rugby) players have focused on professional players. Therefore, data on injuries in collegiate rugby players in Japan is limited. The purpose of this study was to conduct a prospective injury survey of Japanese male collegiate rugby players over several years and to analyze the injuries that occurred during matches and training according to field position, type of injury, and mechanism of injury. This prospective study initially registered 128 rugby players from one university club. The occurrence of injuries was recorded by athletic trainers during the rugby seasons between 2017 and 2019. The total injury rate (IR) was 7.26 injuries/1000 player-hours (1000 PHs). The match IR (122.73 injuries/1000 PHs) was almost 31.9 times higher than the training IR (3.84 injuries/1000 PHs). Ankle sprains/ligament injuries (17.7%; 1.28 injuries/1000 PHs) were the most common injuries, in addition to acromioclavicular joint injuries in forwards and hamstring strain injuries in backs. The most common injury mechanism was tackling (16.4%). Injury characteristics differed according to field position; therefore, preventive measures according to field position are necessary. Moreover, the high number of tackle injuries suggests that improved tackle skills would help reduce injuries. The IR among Japanese collegiate rugby players was higher than that reported previously. Injury prevention training for collegiate players is necessary to reduce the number of injuries.